Isolation and identification of polystyrene degrading bacteria from zophobas morio’s gut - Tan, Kian Meng; Mohd Fauzi, Noor Akhmazillah; Mohd Kassim, Angzzas Sari; A. Razak, Aliff Hisyam; Kamarudin, Kamarul Rahim (2021)
Polystyrene (PS) and expanded polystyrene (EPS) are commodity plastics widely used in many industries. The increase of PS in the environment causes ecological threats. It has been observed that the beetle larvae feed on plastic packages, and this has drawn the researcher’s attention towards the complex system within the larvae’s gut where relationships between fungi, bacteria, and the insect host have been established. The objective of this study is to isolate and identify PS-degrading microbe from super worms. The study used polystyrene as a sole carbon source to isolate the positive PS-degrading bacteria. Five bacterial colonies which showed positive growth on the modified PS-agar plate were isolated. All five colonies of the PS-degrading bacterial isolates were identified using partial 16 S rRNA gene sequencing. The results showed a close relationship between Bacillus aryabhattai and Bacillus megaterium strains. An examination via biochemical studies for distinction was implemented further. Based on the morphological characterization and taxonomic method, the isolates were identified as Bacillus megaterium. The isolates' viability was tested using 2,3,5-triphenyltetrazolium chloride (TTC), and positive results were obtained with red-colored insoluble triphenylformazan (TPF) formed within 5 to 7 days. The isolation and identification of these bacteria from Zophobas morio’s gut may provide a promising source of a plastic degrading enzyme that can be further studied and manipulated in developing enzymatic biodegradation in plastic waste management.